Preventive action and conflict mitigation in Nigeria's 2015 elections. Issue 4 (7th June 2017) - Orji, Nkwachukwu
ABSTRACT: Prior to the 2015 Nigerian general elections, there were concerns that the fierce political contest would lead to electoral violence in the country. However, the elections were conducted peacefully, with fewer disputes and election-related deaths than previous elections. This study accounts for the fall in the level of electoral violence in Nigeria and discusses the lessons that Nigeria's experience presents. It argues that the avoidance of destructive electoral disputes in Nigeria was the result of preventive action taken by the country's electoral commission, civil society groups, and development partners. The specific preventive actions taken include innovations in election administration aimed at enhancing electoral transparency and credibility, election security measures such as early warning and peace messaging, and preventive diplomacy urging the main candidates and the political elite to embrace peace. The key lesson that can be drawn from Nigeria's experience is that a well thought out conflict prevention strategy should be an integral part of electoral governance, especially in countries with a high risk of electoral violence.